Production potential of castor (Ricinus communis L.) intercropping with soybean (Glycine max L.) under irrigated conditions: PRODUCTION POTENTIAL OF CASTOR INTERCROPPING WITH SOYBEAN - P M VAGHASIA; V B BHALU; R H KAVANI (Journal of Oilseeds Research, 2016)
A field experiment was conducted consecutively for three years during rainy seasons of 2010-11 to 2012-13 at the Main Oilseeds Research station, Junagadh Agricultural University, Junagadh on intercropping castor in soybean with an objective to find out suitable intercropping ratio for achieving higher productivity and profitability. The experiment was conducted on mediumclay soil under irrigated conditions. It consisted of eight treatments including sole castor, sole soybean, combinations of intercropping of castor (cv. GCH 7) with soybean (cv. Gujarat soy. 1) in row proportion 1:1 and 1:2 with sowing period of castor 15, 30 and 45 days after sowing of soybean. The results revealed that sowing of castor at 30 days after sowing of soybean in 1:2 ratio recorded significantly higher castor equivalent yield (2806 kg/ha) and land equivalent ratio (LER: 1.72) besides higher net returns (Rs. 69289/ha) and B:C ratio (2.86).